Research on Internet Behavior of students grade 1 - 6 Ban Fang School - Jadjaeng, Parinyawat (Wisdom Journal of Humanities and Social Sciences, 2024)
The research was conducted to examine the internet usage behavior of 104 students in grades 1 through 6 at Ban Fang School during the second semester of the 2022 academic year. A sample of 82 students was collected between November and December 2022 using the Yamane 1972 method for sample size estimation. Data was gathered through a questionnaire developed by the researcher. The findings revealed that the internet usage behavior of students at Ban Fang School was observed to be moderate overall. Particularly, primary school students in grades 1-6 tended to use the internet primarily for entertainment, followed by communication and least for educational purposes. In examining the relationship between the students’ internet usage and their school stipends and cumulative GPA, it was found that the amount of money received from the school was not significantly related to the cumulative GPA. Similarly, the amount of money received from the school did not show a statistically significant relationship with the students’ internet usage. However, the cumulative GPA was found to have a statistically significant relationship with communication and overall internet usage at the .05 level.